Anteseden Penghimpunan Dana Pihak Ketiga Bank Syariah Di Indonesia - Ratna Sari Dewi; Yuni Shara (Jurnal Riset AKuntansi dan Bisnis, 2021)
This study aims to determine the Antecedents of Third Party Funds Collection for Islamic Commercial Banks in Indonesia. This study amounted to 34 Islamic Public Bodies and Sharia Business Units in Indonesia for the period 2015-2018. The sampling technique in this study was purposive sampling. The data analysis technique used multiple linear regression. The results showed that partially the profit sharing and inflation positively and significantly affect third-party funds. The BI interest rate variable has a positive but insignificant effect on third party funds. The variable number of offices has a negative and insignificant effect. Profit-sharing variables, interest rates, inflation, and the number of offices simultaneously significantly affect third-party funds (TPF) of Islamic Commercial Banks in Indonesia.